First Year Students of the School of Management and Entrepreneurship’s Determinants in Course Preference - Claire Fraces C. Barahan; Reymark Pabilando; Mark Erwin S. Duterte; Estelito Salut (International Journal Labs, 2022)
The study on the determinants in course preference of the 50 first year students of the School of Management and Entrepreneurship was conducted in the Biliran Province State University, Naval, Biliran. A descriptive research design was adopted in this study. According to the study' s findings, majority of the students in the School of Management and Entrepreneurship were came from TVL Track during their Senior High School and some are in GAS. It shows that majority of the students taking up BSHM and BSTM are not in the right track. The academic factor had the highest mean of 4.66 interpreted as